An investigation into adhesives to consolidate distemper paintings on canvas - Cristina Castro Simarro (Ge-conservación, 2020)
This article investigates traditional and modern adhesives used to consolidate distemper paintings on canvas, with special reference to sixteenth century Hispano-tüchlein paintings, also called sargas. Such artworks are not only difficult to handle due to their large size, but they are also inherently fragile and/or are highly hygroscopic. This sensitivity is caused in part by the nature of the painting technique as well as the lack of varnish, which might account for why conservation methods related to these works have not been addressed in the past. This investigation was conducted on historical reconstructions samples to assess and develop treatment strategies for distemper paintings, in particular issues linked to powdery/friable matte paint layers. The impact of several adhesives on the painted surface of historical reconstructions was evaluated before and after the samples were subjected to humidity cycling tests using a range of analytical techniques. Such information can be used to aid conservators who face consolidation issues related to underbound paintings or artworks with similar surfaces. The results reveal that there is no one perfect adhesive for matte paint nor one that can be removed completely, once applied. Aquazol® 200 and Funori performed the best, but still introduced changes in colour and gloss, even if minimal.